Characterization and Evolutionary Analyses Reveal Differential Selection Pressures on PGIc and PGIp During Domestication in Castor Bean - Jiayu Guo; Lanxin Jiang; Anmin Yu; Bing Han; Aizhong Liu (Horticulturae, 2025)
Phosphoglucose isomerase (PGI), which catalyzes the interconversion of glucose 6-phosphate (G6P) and fructose 6-phosphate (F6P), plays a key role in regulating carbohydrate synthesis and catabolism in plant growth and development. In higher plants, two PGI isoenzymes, plastidic (PGIp) and cytosolic (PGIc), have diverged significantly in sequence, structure, activity, and functional roles, despite catalyzing the same reaction. However, whether they experience distinct selection pressures during intraspecific population differentiation remains unknown. In this study, we identified the PGIc and PGIp genes in castor beans, an important industrial and horticultural crop, and revealed their different expression patterns across tissues, particularly during seed development. Population genetic analyses (Tajima’s D, ML-HKA, and CODEML) detected strong evidence of positive selection on RcPGIc, but not RcPGIp during domestication. Four positively selected sites in RcPGIc (114T, 310T, 338A, and 613S) were inferred with posterior probabilities > 95% in BEB analysis, and two of them (114T and 613S) were found to be significantly associated with higher seed oil content, suggesting that these two sites could potentially influence oil accumulation in castor seeds. This study provides the first evidence of differential selection pressures on PGIc and PGIp during intraspecific population differentiation, offering new insights into their functional divergence.